An Ideational Metafunction Analysis of President Joko Widodo’s Speech on Crude Palm Oil (CPO) Policies - Putra, Febi Rahmad; Zulprianto; Sawirman (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The purpose of this research is explaining the ideational function of the two speeches by President Jokowi about Crude Palm Oil (CPO) Policies. The design of this research was descriptive qualitative research. The data for this study constituted two speeches President Joko Widodo about crude palm oil (CPO) exports on two different occasions at State Secretariat website (https://www.setneg.go.id) that was obtained by copying and pasting. The speeches were analysed by using systemic functional linguistics methods that is focused to ideational metafunction (experiential meaning and logical meaning). The result of the analysis was both of speech Joko Widodo revealing the similarity. Speech A showed mental process dominant in experiential meaning and speech B also showed mental process dominant. Beside the similarity both of speech, Jokowi speech revealed the differential using participant (senser), speech A used word of pemerintah, and on speech B using word of saya. Using word of pemerintah was a form of Jokowi as President not wanting to be blamed when bad things happen in made crude palm oil’s policy. Therefore, using word of saya was imaging form of Jokowi, because his clause gave profit for his electability. Jokowi was very careful in publishing speech, word of very careful reflected as self-righteousness.